DECONSTRUCTION IN MOVIE ENTITLED GRETEL AND HANSEL - Mayangseto, Ginarsiwi; Winarti, Winarti (Universitas Duta Bangsa Surakarta, 2023)
This study is aimed to find out; 1) Plot deconstruction in Gretel Hansel movie storyline compared to the original story. 2) Characterization of Hansel Gretel deconstruction in Gretel Hansel character movie compared to the original story. The data analysis technique in this study is using literature study technique by collecting dialogue and proofs, then combine with descriptive qualitative as a research method. By using those method and technique, the result shows that the plot has deconstructed Gretel and Hansel movie into horror and thriller atmosphere. The idea was to, look for the opposition binaries and analyse Gretel and Hansel character. The deconstruction of plot take place with the background of Gretel and Hansel where they lived with their mother, without a father and there is no scene when Hansel leaving a mark in a street as used to be in original story. The deconstruction of character also existed on Gretel and Hansel character, where in movie Hansel is innocent, weak, submissive and coward. While Gretel in movie shown has magic power, brave, clumsy and dominant